Language disorders as comorbidity in enuretic children: prevalence and impact on treatment. - Ferrara, Pietro; Mastricci, Rosanna; Cammisa, Ignazio; Matarrelli, Chiara; Gatto, Antonio; Gallo, Giorgia; Roberto, Sacco; Verrotti, Alberto (Acta Biomedica Atenei Parmensis, 2024)
Background and aim:Several studies have recorded an association between nocturnal enuresis (NE) and developmental delays. Language disorders are one of the main comorbidities in enuretic children, affecting therapy outcome and prognosis.Methods:The study was carried out within our pediatric outpatient clinic in Campus Bio-Medico University Hospital Foundation of Rome, enrolling a total of 223 enuretic children, of which 20 with a language disorder. Data concerning NE were collected through questionnaire and interview with parents and a bladder diary. The language disorders was secondary investigated. The chi-squared test was used to evaluate the correlation between therapy outcome and language disorders.Results:Our sample was composed of 223 enuretic children, with a mean age of 7 years. 211 children were subjected to pharmacological treatments, while 12 children, with mild clinical symptoms, did not take any drugs. It was observed that 48,5% of enuretic children did not respond to therapy or relapsed, while 43% responded in the first cycle. 20/223 (9%) of enuretic children had a language disorder, of which 17 subjected to pharmacological therapy: 13/17 (76,5%) did not respond to therapy and 4/17 (23,5%) responded (p = 0.038).Conclusions:Language disorders could impact NE therapy response, underlying the influence of comorbidities and the importance of a global assessment in enuretic children.